Phytochemical and nanoparticle-based therapeutic potential of Sphaeranthus indicus against hepatocellular carcinoma via cryptomeridiol targeting - Konduskar, Ritika Ravindra; Patil, Abhinandan R.; Bhinge, Somnath D.; Chawla, Gourav Rameshlal; Yadav, Yash Bhagavan (Frontiers in Oncology, 2025)
BackgroundCancer remains a major global health challenge, and despite advances in chemotherapy, there is a need for safer plant-derived therapeutics. Sphaeranthus indicus (Si) (East Indian globe thistle), traditionally used in herbal medicine, exhibits anticancer potential. This study evaluated the cytotoxic activity of Si alcoholic extract, its bioactive fraction, and biosynthesized silver nanoparticles (SiAgNPs) against hepatocellular carcinoma (HepG2) cells.MethodsAlcoholic extract of Si extract was fractionated, and GC–MS identified cryptomeridiol as the major bioactive compound. Structural confirmation was performed using IR, ^1H NMR, and UV–Vis spectroscopy. SiAgNPs were synthesized using Si extract and characterized by UV–Vis, FTIR, FESEM, and XRD. Cytotoxicity was assessed by CCK-8 assays, while apoptosis was confirmed morphologically. Molecular docking evaluated the binding of cryptomeridiol with hepatocellular carcinoma-associated protein targets (PDB IDs: 8QAL, 8QAN, 8QAP, 8QAR, 8QAZ).ResultsIR spectra confirmed hydroxyl and olefinic functional groups in cryptomeridiol, while ^1H NMR showed characteristic methyl, methylene, hydroxyl methine, and olefinic proton signals. SiAgNP formation was indicated by a color change (yellow → brown) and a surface plasmon resonance peak at 437 nm. FTIR of SiAgNPs revealed reduced intensities of O–H, C=O, and C–O bands, confirming phytochemical involvement in nanoparticle stabilization. FESEM showed spherical nanoparticles with an average size of 38.35 ± 16.42 nm, and XRD analysis confirmed their crystalline FCC structure with a crystallite size of ~16.8 nm. Cytotoxicity assays demonstrated IC50 values of 44.93 μg/mL (Si extract), 43.87 μg/mL (cryptomeridiol), and 42.16 μg/mL (SiAgNPs), comparable to 5-fluorouracil (43.16 μg/mL). All treatments inhibited HepG2 proliferation by >75% and induced apoptosis-like morphological changes. Molecular docking revealed cryptomeridiol interacted strongly with all selected protein targets, with binding energies ranging from −7.1 to −8.1 kcal/mol, involving hydrogen bonds, alkyl, and van der Waals interactions.ConclusionSi extract, cryptomeridiol, and SiAgNPs are well-characterized, biologically active agents that induce apoptosis and inhibit HepG2 proliferation. These findings highlight cryptomeridiol as a potent phytochemical scaffold and demonstrate the translational potential of combining phytochemicals with nanotechnology for hepatocellular carcinoma therapy through the in-vitro model.